Drugs in South Asia: from the opium trade to the present day - Emdad-ul Haq, M. (Imprint: Palgrave Macmillan, 2000)
The drug problem in South Asia is mounting. This work provides an inside story of the pro-revenue drug policies pursued both by the British colonial authorities and post-independent governments in South Asia. It examines the resurgence of Indian traffickers in international drug trafficking in recent years, and presents an extensive overview of the Afghan crisis that endorsed money from heroin trafficking to support the war in Afghanistan. The dangers of the drug trade in South Asia have now become global - the author assesses international efforts against drug trafficking and the factors constraining this.